Culture and career development - Johns, Nick (International journal of contemporary hospitality management ;, 2007)
This e-book deals with aspects of culture and career development in hospitality and tourism management. Many studies have assumed the importance of cultural values and/or personality in the service orientation of individuals. The findings presented here, however, emphasize the importance of training and development in preparing individuals to give service. This is heartening to the industry, which faces increasing challenges through globalization and immigration. From these studies it seems that not only can the predisposition to service as a whole be fostered by training, but also front line.